Trends in incidence of oral anticoagulant-related intracerebral hemorrhage and sales of oral anticoagulants in Capital Region of Denmark 2010–2017. (June 2021) - Grundtvig, Josefine; Ovesen, Christian; Havsteen, Inger; Christensen, Thomas; Gaist, David; Iversen, Helle K; Kruuse, Christina; Lilja-Cyron, Alexander; Ægidius, Karen; Rosenbaum, Sverre; Meden, Per; Marstrand, Jacob; et al.
Introduction: Non-vitamin K-antagonist oral anticoagulants (NOAC) have become first choice oral anticoagulant (OAC) with decreasing use of vitamin K antagonists (VKA), partly due to lower risk of intracerebral hemorrhage (ICH). Aim: to identify trends in sale of OACs and relate them to trends in OAC-related ICH (OAC-ICH). Patients and methods: Study was based on the population in the Capital Region of Denmark (1.8 million inhabitants). We identified all patients admitted with a non-traumatic OAC-ICH in 2010–2017 and ascertained diagnosis and drug use through medical charts. We used information available in the public domain on sale of defined daily doses (DDD) of OAC in the Capital Region of Denmark. Results: 453 patients with OAC-ICH out of a total of 2877 ICH-events were identified. From 2010 to 2017 sale of NOAC rose from 0.1 to 11.8 DDD/1000 inhabitants/day (p < 0.001); while VKA sale decreased from 7.6 to 5.2 DDD/1000 inhabitants/day (p < 0.001). The total number of ICH events was stable between 2010 and 2017, but the proportion of OAC-ICH events increased from 13% in 2010 to 22% in 2017 (p < 0.001). The proportion of ICH events related to NOAC had a significant increasing trend (p < 0.001), whereas a decreasing trend was observed for VKA (p = 0.04). Discussion: In Denmark, the population on OACs has increased; resulting from increased use of NOACs. Parallel to this development, the proportion of OAC-ICH overall has increased based on an increasing trend in NOAC-related ICH. Conclusion: Our findings document a need for further research on prevention and treatment of this complication.